ANALISIS STRUKTUR BIAYA DAN PEMASARAN USAHATANI JAGUNG MANIS (Zea mays L. Saccharata ) - Noor Afriani; Etty Wahyuni MS (J-PEN Borneo : Jurnal Ilmu Pertanian, 2022)
AbstractSweet corn commodity has good prospects for development, but there are various problems in the sweet corn farming agribusiness system, namely the weak linkages between upstream to downstream subsystems such as distribution and supply of production factors, agricultural production processes, processing and marketing as well as risks to income. This study aims to analyze the cost structure, marketing channels and marketing efficiency of Sweet Corn (Zea mays L. Saccharata) in Tarakan City. Respondents obtained by purposive sampling method from sweet corn farmers in Tarakan City amounted to 112 people. Data analysis to answer existing problems includes analysis of cost structure, marketing channels, marketing margins, farmer's share and marketing efficiency. The results showed that variable costs gave the highest contribution to total production costs of 61.39% compared to fixed costs of 38.61%, with the highest percentage being labor costs. The marketing channel consists of 2 marketing channels, namely marketing channels that involve 1 marketing agency, namely market traders to consumers and marketing channels that involve 2 marketing institutions, namely collectors and market traders. Marketing channels 1 and 2 are in the efficient category based on the farmer's share value, namely 82% for channel 1 and 72% for channel 2. Key words: the cost structure, marketing, sweet corn AbstrakKomoditas jagung manis memiliki prospek yang baik untuk dikembangkan, namun terdapat berbagai permasalahan dalam sistem agribisnis usahatani jagung manis yaitu lemahnya keterkaitan antar subsistem hulu sampai ke hilir seperti distribusi dan penyediaan faktor produksi, proses produksi pertanian, pengolahan dan pemasaran serta risiko pada pendapatan. Penelitian ini bertujuan untuk menganalisis struktur biaya, saluran pemasaran dan efisiensi pemasaran Jagung Manis (Zea mays L. Saccharata) di Kota Tarakan. Responden diperoleh berdasarkan metode purposive sampling dari para petani jagung manis di Kota Tarakan berjumlah 112 orang. Analisis data untuk menjawab permasalahan yang ada meliputi analisis struktur biaya, saluran pemasaran, margin pemasaran, farmer’s sharedan efisensi pemasaran. Hasil penelitian menunjukkan biaya variabel memberi kontribusi tertinggi terhadap total biaya produksi sebesar 61,39% dibandingkan biaya tetap sebesar 38,61%, dengan persentase tertinggi adalah biaya tenaga kerja dan biaya pupuk. Adapun saluran pemasaran terdiri dari 2 saluran pemasaran yaitu saluran pemasaran yang melibatkan 1 lembaga pemasaran yaitu pedagang pasar ke konsumen dan saluran pemasaran yang melibatkan 2 lembaga pemasaran yaitu  pengepul dan pedagang pasar. Saluran pemasaran 1 dan 2 termasuk kategori efisien berdasarkan nilai farmer’s share yaitu 82% untuk saluran 1 dan 72% untuk saluran ke 2.Kata kunci: struktur biaya, pemasaran, jagung manis